2014
DOI: 10.1111/jsm.12397
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multiple Sclerosis on Female Sexuality: A Controlled Study

Abstract: Aim The aim of this study was to investigate the effects of multiple sclerosis (MS) on female sexuality. Methods Present study included 142 females (70 MS patients, 72 healthy controls). MS patients were evaluated by Expanded Disability Status Scale (EDSS) for functional status, by Beck Depression Inventory (BDI) for severity of depression, by Visual Analog Scale (VAS) for severity of pain, and by Female Sexual Function Inven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
52
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 38 publications
(55 reference statements)
8
52
0
2
Order By: Relevance
“…Finally, sexual dysfunction may results from psychological factors as well. Sexual dysfunction was positively correlated with depression in several studies (Gumus et al, 2014;Lew-Starowicz and Rola, 2014). Given the great impact of sexual dysfunction in the social life of MS patients, this association is not surprising.…”
Section: Sexual Dysfunctionmentioning
confidence: 77%
See 1 more Smart Citation
“…Finally, sexual dysfunction may results from psychological factors as well. Sexual dysfunction was positively correlated with depression in several studies (Gumus et al, 2014;Lew-Starowicz and Rola, 2014). Given the great impact of sexual dysfunction in the social life of MS patients, this association is not surprising.…”
Section: Sexual Dysfunctionmentioning
confidence: 77%
“…The existence of any impact of relapses on sexual dysfunction is still debated, since conflicting results were obtained by different authors (Mattson et al, 1995;Zorzon et al, 2001). Other authors also found that sexual dysfunction correlates positively with bladder dysfunction (Gumus et al, 2014;Lew-Starowicz and Rola, 2014). Finally, sexual dysfunction may results from psychological factors as well.…”
Section: Sexual Dysfunctionmentioning
confidence: 86%
“…Gumus et al. have found negative correlations for Female Sexual Function Index (FSFI) score with Beck Depression Inventory (BDI) score, Expanded Disability Status Scale (EDSS) score, pain, age, and disease duration, as well as a positive correlation with the level of education, in a sample of 70 MS women [12]. The negative correlation of BDI score with SF was confirmed by Mohammadi et al.…”
Section: Introductionmentioning
confidence: 82%
“…In 2006, a survey of 4,267 patients with MS living in the United States found that perception of body image worsened if the patient was less educated, female, had a longer disease duration, and a greater degree of disability [4]. Another study found that the number of sexual encounters per week was lower in women with MS compared to the general population [5]. These findings suggest that predictors of sexual dysfunction in women with MS are diverse and multifactorial.…”
Section: Effect Of Ms On Pregnancy Sexual Dysfunctionmentioning
confidence: 94%
“…Several studies have informed our current understanding of the influencing factors and consequences of sexual dysfunction in women living with MS [1][2][3][4][5]. In 2006, a survey of 4,267 patients with MS living in the United States found that perception of body image worsened if the patient was less educated, female, had a longer disease duration, and a greater degree of disability [4].…”
Section: Effect Of Ms On Pregnancy Sexual Dysfunctionmentioning
confidence: 99%